The Phenomena of Organizational Structure Change as Change Factor of Financial Consultant’s Motivation - Poerbonegoro, Galuh Adhitia; Setiawan, Margono; ., Sudjatno (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2017)
Life insurance has developed into an attractive industry and has an important role in supporting businesses, families and communities. It grew into a business commodity that attracted many people. Competition in the life insurance industry is increasingly complex and competitive due to the number of life insurance companies made a lot of customers have many choices that requires every company to be more responsive to acquire customers, to support the organizational change, motivation and performance of employees. According to the first interview with top management, obtained information that there is a distance between superiors and subordinate in Allianz Life Indonesia’s new system, where Business Partner (leader) only served to control Business Executive and give freedom to the actions carried out by subordinates so that the relationship between them is less synergy. The purpose of research is to describe implementation strategies and the impact of OSC to Financial Consultant’s motivation. This study uses a qualitative research method. Research results obtained implementation strategy of OSC, which influenced by factors such as the driver of an effective and efficient work system, increasing of industry competition, and maintaining customer trust. There are two impact to Financial Consultant’s motivation include intrinsic motivation and extrinsic motivation.Keywords: Insurance, Organizational Structure Change, Motivation, Financial Consultant